(untitled) - Gonzáez-Elipe, A. R; Sanz, J. M (London, 2003)
Includes bibliographical references and index.
Keywords: Ion bombardment; Thin films -- Design and construction.; Thin films -- Effect of radiation on.; Màng mỏng -- Thiết kế và xây dựng; Màng mỏng -- Ảnh hưởng của bức xạ